A 30‐year study of homicide recidivism and schizophrenia. (5th August 2013) - Golenkov, Andrei; Large, Matthew; Nielssen, Olav
ABSTRACT Background A second homicide by a released mentally ill person is a potentially avoidable tragedy that can reduce the prospects of conditional release for other mentally ill offenders. Aim The aim of this study was to compare the clinical and criminological features of single and recidivist homicide offenders with schizophrenia from the Chuvash Republic of the Russian Federation. Methods Data were extracted from the criminal and clinical records of all people with schizophrenia who had been convicted of a homicide in the Chuvash Republic at any time between 1 January 1981 and 31 December 2010. Those convicted of a second homicide offence during the 30 years of the study were compared with those convicted of a single homicide. Results Sixteen (10.7%) of 149 homicide offenders with schizophrenia had committed a previous homicide. The 16 recidivists included nine offenders who were diagnosed with schizophrenia at the time of their first homicide (after January 1981), three who were diagnosed with schizophrenia only after the first homicide and four who had already been diagnosed with schizophrenia at the time of a pre‐1981 homicide. Time at risk for recidivists and non‐recidivists differed, but the average time back in the community for the non‐recidivists just exceeded the average time to second homicide for the recidivists. All the recidivists were men. Living in a rural area and dissocial personality traits were associated with homicide recidivism. Conclusions and implications for practice In the Chuvash republic, most of the repeat homicide offences by people with schizophrenia were committed by people residing in rural areas with less access to psychiatric services, which provides indirect evidence for the efficacy of ongoing treatment and supervision in preventing repeat homicides. This area of study is, however, limited by the small numbers of cases and the long follow‐up required. International collaborative studies are indicated to provide a more accurate estimate of the rate of recidivist homicide in schizophrenia. Copyright © 2013 John Wiley & Sons, Ltd.